Evaluation of Employee Performance on Transformational Leadership and Organizational Commitment with Job Satisfaction as a Mediator - Sari, Selvi Yona; Nadilla, Nia (UPI YPTK Journal of Business and Economics, 2024)
This study aims to determine how much influence Transformational Leadership and Organizational Commitment have on Employee Performance with Job Satisfaction as Intervening Variables at the Bukittinggi City Education Office. The data analysis method used a questionnaire, with a sample of 67 respondents. The method used is Structural Equation Modeling (SEM) with Partial Least Square (PLS) 4.0. By circulating the questionnaire as many as 67 respondents. The results of the data analysis concluded that (a) transformational leadership had a positive and significant effect on job satisfaction with a significant level (0.000>0.05) (b) organizational commitment had a positive and significant effect on job satisfaction with a significant level (0.011 <0.05) ( c) transformational leadership has a positive and insignificant effect on employee performance with a significant level (0.128 > 0.05) (d) organizational commitment has a positive and insignificant effect on employee performance with a significant level (0.188 > 0.05) (e) job satisfaction has a positive and significant effect on employee performance with a significant level (0.000 <0.05) (f) transformational leadership has a positive and significant effect on employee performance through job satisfaction with a significant level (0.000 <0.05) (g) organizational commitment has a positive effect and significant to employee performance through job satisfaction with a significant level (0.012 <0.05